Maximize mining exploitation efficiency of the quarry: a case study (Rudarsko-geološko-naftni zbornik, 2021)
Nowadays, the dimension stone industry performs a crucial role in the world economy. Accordingly, dimension stone quarries' importance grows due to their different applications in various construction, building, and decorative industries. Some issues threaten this industry and provide a financial risk that should be taken into account to make the risk least for investment. The presence of discontinuities in the rock mass has a key function as far as it concerns the overall quality of in situ rock blocks. It impacts the feasibility of dimension stone quarries and overall mine exploitation efficiency. Therefore it is recommended to survey discontinuities and rock blocks and estimate the average geometry of a rock block, including the shape and size, before mining the benches to maximize mining exploitation efficiency and minimize waste ore production. This investigation aims to survey the discontinuities of the limestone quarry mine located in Josheghan, Iran, to determine and calculate rock blocks' suitable geometry and extraction’s direction for active mine benches. For this purpose, the Scanline method was applied to survey discontinuities in seven active benches. 3DEC software was used to indicate discontinuities and model the rock blocks for all active benches. It was concluded that the benches' cutting line make a 13.14 degree with the discontinuities main's direction. The result of this study proved that by changing the direction of mining and extraction for active mine benches, the unnecessary waste production would decrease. The production rate with the recommended extraction direction will increase by about 1.13% compared to the current extraction direction, which makes 13.14 degrees with the discontinuities main's direction. Currently, bench seven recorded The Minimum production rate, which is 97.60; by applying the new extraction's direction, it is predicted that this bench will achieve a 99.83 production rate. Consequently, it is concluded by improving the production rate, exploitation efficiency would increase considerably.